Dolutegravir: Pharmacokinetics and Pregnancy Profile - Gudisa Bereda (International Journal of Chemotherapy Research and Practice, 2022)
Dolutegravir suppresses this integration enzyme, so human immune virus can’t create every greater copies of itself, thus ‘’integrase inhibitor.’’ Dolutegravir is hastily absorbed pursuing oral administration. The median maximum plasma concentration is reached 1.5–2.5 hours after oral uptake with a mean half-life of 12–15 hours, rendering feasible for once-daily dosing without the need for pharmacological boosting. The terminal half-life is about 14 hours. The apparent oral clearance is about 1 liter/hour. Fifty three percent of the total oral dose of dolutegravir is excreted unchanged in the feces, thirty two percent through urine as glucuronide (eighteen percent) or alkylated product (three point five percent), and other organic conjugated products sequencing from phase II liver metabolisms. Dolutegravir’s categorized as pregnancy category B (no confirmation of pitfall in humans) means either animal-reproduction inquests have not substantiated a fetal peril but there are no restrained inquests in pregnant women or animal-reproduction inquests have reveal an adverse effect (distinctive than a de-escalate in fertility) that was not inveterate in restrained inquests in women in the first trimester (and there is no confirmation of a pitfall in later trimesters) or there is survey in animal that revealed the medication is safe in pregnant animal, but there is no fetal pitfall confirmation in pregnant women.Antiviral Pregnancy Registry (APR) revealed that as of January 2017, pregnancy outcomes and birth defects were analyzed from 142 pregnancies with reported exposure to DTG during pregnancy. There were 128 live births reported (3 terminations, 11 miscarriages, no stillbirths). Only 4 (3.0%) reported birth defects, which is similar to the expected rate of birth defects in the general population. European Pregnancy and Paediatric HIV Cohort Collaboration (EPPIC) displayed that as of July 2017, 101 pregnancies with exposure to DTG had been identified with 84 birth outcomes. Rates of preterm delivery and “small for gestational age” were identical to outcomes reported from women on alternative regimens (standard of care in the United Kingdom of Great Britain and Northern Ireland).
Keywords: Dolutegravir